Extra-Anatomic prosthetic bypass grafts in management of Sub-inguinal vascular infections - AL-Assal *, Muthanna D.R. ,; .Jaber **, Sabah N,; Nemat**, Mohammed H.,; Hussien**, Uday (AL-Kindy College Medical Journal, 2014)
Infection at the site of vascular anastomosis is a serious complication of vascular surgery and is associated with a high limb loss and mortality rate. The classical method of management is ligation of the injured artery, adequate wound debridement and restoration of circulation. The latter is achieved by either in situ or extra-anatomic bypass. If the distal circulation is not maintained, subsequent amputation is most likely. Objectives: In this study we tried to assess the efficacy of extra-anatomic synthetic bypass grafts in the treatment of vascular infection in the groin to save the limb and avoid the inevitable amputation. Methods: Between January 2006 and December 2007, ten male patients aged twenty to thirty five years (mean=27.3years), with previous vascular surgery (reversed saphenous vein grafting) for sub-inguinal penetrating injuries complicated with infection and bleeding were admitted and managed surgically in the Department of Thoracic and Vascular Surgery, Surgical Specialties Hospital, Medical City Teaching Complex, Baghdad. These patients were studied retrospectively regarding their demographic and clinical features as well as details of the operative procedures and surgical outcome. All patients received emergency wound debridement, arterial ligation and extra-anatomic synthetic (PTFE) bypass grafts (External iliac or common femoral to distal superficial femoral or popliteal artery, six routed laterally and four routed medially in the thigh away from the original surgical field). Results: Excellent results were obtained in nine patients who saved amputation while one patient ended with above knee amputation. No mortality recorded. Conclusion: Extra-anatomic bypass is a useful approach in dealing with infected and disrupted vascular anastomosis and can be used in emergency as well as elective situations as mentioned in most literatures.